Transformasi Orientasi Pemustaka Pada Tahun Politik Pemilu 2024 - Agung Nugrohoadhi (Indonesian Journal of Library and Information Science, 2023)
The need for information for human beings has its own characteristics and differences so that each has an unequal portion in needing the necessary information. They need information because it is considered to be able to add insight so that they can move their minds and behavior to find answers to their ignorance. The development of information through various existing sources causes an abundance of information that is not necessarily all that is needed. The need for this information depends on the background and limited information available at the time. Other implications of the advancement of digital technology will have various impacts. Starting from cultural changes that have shifted the cultural fabric of society that has lived in the midst of Indonesian society for a long time, to information technology that makes information sources very accessible to the public with content diverse content, both from a positive side that can build human civilization or it will plunge humanity into a moral decline that was previously upheld. Shifting moral values ​​into something that must be "sacrifice" advances in information technology. The purpose of writing is to provide competency support for librarians to face the era of information technology. Libraries in the development of increasingly developing technology, it is even not impossible that metaverse technology will help with tasks related to librarianship, causing librarians to improve themselves in facing the transformation of services with users who are increasingly critical due to the environmental situation. their lives with a variety of information that can be accessed through social media, so Librarians must position themselves as facilitators in information dissemination by prioritizing information literacy so they can sort and choose sound information